Analysis of Factors Influencing Customer Decisions in Choosing Deposit Products with Mudharabah Contracts at Bprs Al- Wasliyah Medan - Dinda Dewi Rahma Wijaya; Nurul Inayah; Muhammad Syahbudi (Sekolah Tinggi Ilmu Ekonomi Amkop Makassar, 2025)
This study aims to analyze the influence of promotion , service , and trust on customer decisions in choosing deposit products with mudharabah contracts at BPRS Al- Wasliyah Meldan . The background of this study is based on fluctuations in the number of lending and the nominal mudharabah deposits in the last few years , which indicates the need to identify factors that influence customer decisions . With a population of 128 customers and a sample of 97 people , the number of samples is determined based on the Slovin formula with a Margin of Error of 5%. Clearly , the selected data is primary data with a Likert scale questionnaire data collection methods . The data were analyzed using validity , reliability , classical assumption test , multiple linear regression , and hypothesis test (t- test) and F -test ). The results of the study showed that partially the trust variable had a significant effect on customer decisions , while promotion and service did not have a significant effect . However , simultaneously , the three variables had an effect on customer decisions . The value of the correlation coefficient (R²) of 0.219 showed that 21.9% of the variation in customer decisions could be explained by the three independent variables . These findings highlights the importance of building and maintenance customer trust , as various factors influence the decision to choose mudharabah deposits at BPRS Al- Wasliyah Meldan